2020
DOI: 10.1186/s13006-020-00272-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the barriers and facilitators to the acceptability of donor human milk in eastern Uganda – a qualitative study

Abstract: Background: Human milk is the best nutrition for all infants. When the mother's own milk is not available, the World Health Organization recommends the use of donated human milk and milk banking for neonates born prematurely or with medical problems. Donor human milk is rarely available in low-resource settings where both the rates of preterm birth and neonatal mortality are highest. The potential to reduce neonatal mortality through use of donated human milk is one that is yet to be fully explored in the Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 21 publications
2
24
1
Order By: Relevance
“…Furthermore, healthcare workers are the most likely people to encourage mothers to use donated milk [ 19 ]. It was also reported that in this area, caregivers mostly rely on healthcare workers, who advise them on accurate information that is most beneficial for their infants [ 34 ]. Hospital-based education and increased awareness in the community are definitely imperative, and must occur during antenatal visits [ 23 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, healthcare workers are the most likely people to encourage mothers to use donated milk [ 19 ]. It was also reported that in this area, caregivers mostly rely on healthcare workers, who advise them on accurate information that is most beneficial for their infants [ 34 ]. Hospital-based education and increased awareness in the community are definitely imperative, and must occur during antenatal visits [ 23 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that in this area, caregivers mostly rely on healthcare workers, who advise them on accurate information that is most beneficial for their infants [ 34 ]. Hospital-based education and increased awareness in the community are definitely imperative, and must occur during antenatal visits [ 23 , 34 ]. In order to reach the maximum donor population, awareness of breastmilk donation should be emphasised in society using numerous means such as mass communication, Non-Governmental Organizations (NGOs), and social clubs, which can play a role in motivating donors [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted in African countries 28 have identified similar ‘complex’ 29 or ‘gendered’ 30 decision-making processes that can delay pregnant women’s search for care and determine the acceptance of maternal health interventions. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted in African countries 28 have identified similar 'complex' 29 or 'gendered' 30 decision-making processes that can delay pregnant women's search for care and determine the acceptance of maternal health interventions. 31 Beyond husband's and relatives' perspectives, pregnant women's perceptions of SP for use in IPTp also shape their acceptance of the C-IPTp strategy. The perception that SP can induce adverse effects was a recurrent finding throughout the study that is mirrored in other qualitative studies on MiP prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation